2015
DOI: 10.1155/2015/230985
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Interspecific Hybrid betweenBrassica napusandB. rapaReveals Heterosis for Oil Rape Improvement

Abstract: The hybrid between Brassica napus and B. rapa displays obvious heterosis in both growth performance and stress tolerances. A comparative transcriptome analysis for B. napus (AnAnCC genome), B. rapa (ArAr genome), and its hybrid F1 (AnArC genome) was carried out to reveal the possible molecular mechanisms of heterosis at the gene expression level. A total of 40,320 nonredundant unigenes were identified using B. rapa (AA genome) and B. oleracea (CC genome) as reference genomes. A total of 6,816 differentially ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…Zhang et al . observed that coexistence of multiple gene actions cause oil rape improvement in Brassica 39 . Similarly, in our study, we also identified one important transcription factor WRI1 and lipid related genes showing additive mode in hybrid Tenera , which implies heterosis regulation every node of the gene regulation network in a hybrid.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al . observed that coexistence of multiple gene actions cause oil rape improvement in Brassica 39 . Similarly, in our study, we also identified one important transcription factor WRI1 and lipid related genes showing additive mode in hybrid Tenera , which implies heterosis regulation every node of the gene regulation network in a hybrid.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome analysis as a powerful tool facilitates the identification of DEGs with their expression level and regulatory mechanisms. Previous investigations identified various heterotic DEGs related to a variety of traits between hybrids and parents in plants and animals 13,31,52,53 . Heterotic genes are robust due to multiple allelic combinations between genomes of two parents in both cross and reciprocal cross combinations suggesting that major genes genetically govern this phenomenon 31,54 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the majority of the commonly expressed DEGs revealed non-additive effect especially overdominance (transgressive up-and down-regulation) mode of gene expression patterns in both cross combinations (Table 2). Thus, overdominance mode of gene expression patterns might contribute more than the additive as well as dominance effects to intraspecific heterosis between hybrids and parents in L. longiflorum 52 . (2020) 10:9082 | https://doi.org/10.1038/s41598-020-65909-x www.nature.com/scientificreports www.nature.com/scientificreports/ Functional analysis placed the 260 DEGs into 45 subcategories (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the change of gene expression provides another source of phenotypic novelty [8]. There is growing evidence that merging of two divergent genomes during hybridization can result in the remodeling of parental gene expression patterns in hybrids, a phenomenon called "transcriptome shock" [9][10][11][12]. As manifestations, many genes would be non-additively expressed in hybrids (diverge from the mid-parental value), which contribute to their transgressive phenotypes at some extent [13,14].…”
Section: Introductionmentioning
confidence: 99%